2006
DOI: 10.1080/10428190600881421
|View full text |Cite
|
Sign up to set email alerts
|

MDR-1, but notMDR-3gene expression, is associated with unmutated IgVHgenes and poor prognosis chromosomal aberrations in chronic lymphocytic leukemia

Abstract: Two P-glycoprotein (P-gp) genes, MDR-1 (ABCB1) and MDR-3 (ABCB4), have been identified in humans. This study was designed to investigate whether associations exist between expression of MDR-1 and MDR-3 P-gp and other markers of poor prognosis and/or prior exposure to therapeutic agents in chronic lymphocytic leukemia (CLL). IgVH mutational status, gene usage, CD38 positivity, FISH analysis and clinical information were available on all patients. Twenty-one of 101 patients tested showed MDR-3 P-gp positivity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…A new member of the ABC superfamily, ABCB4 possesses 80% homology to ABCB1. It is suggested that ABCB4 plays a supplementary role to ABCB1 in chronic lymphocytic leukemia (CLL) drug resistance (3) and might have an independent role in MDR in chronic lymphoproliferative disorders (CLPDs) (4,5). To date, however, ABCB4 expression has rarely been studied in AML.…”
Section: Introductionmentioning
confidence: 99%
“…A new member of the ABC superfamily, ABCB4 possesses 80% homology to ABCB1. It is suggested that ABCB4 plays a supplementary role to ABCB1 in chronic lymphocytic leukemia (CLL) drug resistance (3) and might have an independent role in MDR in chronic lymphoproliferative disorders (CLPDs) (4,5). To date, however, ABCB4 expression has rarely been studied in AML.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with other PB hematopoietic lineages and CD34-positive precursor cells; there was an expression proWle in normal and CLL B cells that was characterized by positivity for MDR1, MDR2, MRP1, MRP4, MRP5, and MRP7. MDR1 expression has previously been correlated to unmutated IgV H gene status and a poor prognosis in CLL (Matthews et al 2006). This observation was, however, not conWrmed in a cell population positive for ZAP70 (Guillaume et al 2007), which is a surrogate marker for unmutated IgV H status (Crespo et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Both genes are overexpressed in CLL, and MDR1 has been associated with advanced clinical stages Sonneveld et al 1992). Furthermore, a correlation of MDR1 and MDR2 expression with unfavorable IgV H status and cytogenetic aberrations has been described (Matthews et al 2006). …”
Section: Introductionmentioning
confidence: 97%
“…[89] Concerning MDR3, a correlation of this protein and shorter survival has been described in CLL patients. [90] It has also been reported that MDR3 positivity may be associated with a more malignant phenotype in CLL, although this pattern was not observed with MDR1 positivity. [91] …”
Section: Constitutive Nucleoside-derived Drug Transport Activities Inmentioning
confidence: 93%